Observation of X(3872) production in pp collisions at $\sqrt{s}=7~TeV$ - The LHCb Collaboration; R. Aaij; C. Abellan Beteta; B. Adeva; M. Adinolfi; C. Adrover; A. Affolder; Z. Ajaltouni; J. Albrecht; F. Alessio; M. Alexander; G. Alkhazov; et al. (European Physical Journal C: Particles and Fields, 2012)
Abstract Using 34.7 pb−1 of data collected with the LHCb detector, the inclusive production of the X(3872) meson in pp collisions at $\sqrt{s}=7~TeV$ is observed for the first time. Candidates are selected in the X(3872)→J/ψπ + π − decay mode, and used to measure where σ(pp→X(3872)+anything) is the inclusive production cross section of X(3872) mesons with rapidity in the range 2.5–4.5 and transverse momentum in the range 5–20 GeV/c. In addition the masses of both the X(3872) and ψ(2S) mesons, reconstructed in the J/ψπ + π − final state, are measured to be $$m_{X(3872)} = 3871.95 ±0.48 \ (stat) ±0.12 \ (syst)\ MeV/c^2 $$ and $$m_{ψ(2S)} = 3686.12±0.06 \ (stat) ±0.10 \ (syst)\ MeV/c^2. $$